Factors influencing the value of CPD activities among VET teachers - Per Andersson; Mattias Hellgren; Susanne Köpsén (International Journal for Research in Vocational Education and Training (IJRVET), 2018)
Context: Teachers in vocational education and training (VET teachers) have specific conditions for their continuing professional development (CPD). They have a background in an initial occupation, in which they now teach and train the next generation. Thus, as VET teachers, they are expected to master the knowledge and skills of that occupation, even if they have now crossed the boundary from the community of their initial occupation to the community of the school. This study explores the perceived values among VET teachers of different activities that may contribute to their CPD in teaching subjects/initial occupations. The study examines VET at the upper secondary level in Sweden. Here, the VET teachers have the main responsibility for students' vocational learning in the vocational subjects, including the work-based parts. In the latter parts, the teachers are supplemented by supervisors at the workplace. Approach: We argue for the duality of a VET teacher identity with a professional competence that comprises two intertwined parts – teaching skills, and knowledge of the teaching subjects based in the teachers' initial occupations. Our study is based on a situated learning perspective, and the empirical findings particularly concern values created from learning through participation and boundary crossing. CPD activities typically include some form of participation in and/or boundary crossing between school and work-life practices. In the analysis we also include the possible influence of institutional, situational, and dispositional drivers and barriers for participation in different activities. The research question was: what factors can explain the variation in perceived values created by participation in different CPD activities among VET teachers? The study was conducted as a survey of 886 Swedish VET teachers. Focus was put on the values created through different types of activity, values for the teachers' vocational knowledge, for networks in working life, and for teaching. The data were primarily analysed using logistic regression modelling. Findings: Dispositional drivers, the teacher's sex, and regular performance of the activity are important for the perceived value. The dispositional factor is the one most commonly retained, and it has a consistently positive effect. Factors such as educational background and vocational training have weaker influence, which suggests that individual driving factors are important when VET teachers assess the value of CPD activities. Conclusions: The study covers a general challenge for VET teachers, but is of particular relevance in systems with a high degree of school-based VET, full-time employed VET teachers, and VET teachers who are responsible for students' vocational learning. Here, the values for vocational knowledge, for networks, and for teaching that are created through different activities are important for the VET teacher identity. They are also interrelated, and together they provide professional development in relation to the initial occupation, and for the occupation as a vocational teacher.
Keywords: 330; VET; Vocational Education and Training; Continuing Professional Development; Value Creation; Vocational Teachers; Staff Development